مبدأ الشرعية في الفقه الجنائي الإسلامي وما يحققه من ضمانات للمتهم: دراسة فقهية قانونية مقارنة - التميمي، عماد محمد رضا علي; الفقير، رائد سليمان (جامعة العلوم الإسلامية العالمية - عمادة البحث العلمي, 2016)
يخضع القانون الجنائي-في عصرنا الحاضر-وبمختلف فروعه لمبدأ الشرعية، ذلك لان القانون يتتبع الواقعة الجرمية منذ تجريمها ومن ثم تقريره العقوبة الملائمة لارتكابها مرورا بملاحقة المتهم بالإجراءات اللازمة ونحوها انتهاء بالأشراف القضائي على تنفيذها، كل ذلك يتم تحت مظلة مبدأ الشرعية حتي لا يتعدى أحد- بحجة حماية أمن المجتمع-على الحوق التي كفلتها الشرائع السماوية والدساتير الأرضية في دول العالم المختلفة، وعل رأس هذه الحقوق الحرية والكرامة، فجاء هذا البحث ليسلط الضوء على هذا المبدأ من الناحية الشرعية، وما يحققه من ضمانات للمتهمين تكفل لهم الحفاظ على حقوقهم من أن تهدر أو تستباح لحجج واهية لا تستند إلى اليقين.
The criminal law with all its branches at present is governed by the principle of legitimacy. The law traces the criminal event since it is convicted and then comes up with the proper punishment. This is conducted through pursuing the criminal by the required procedures and ending up with the judicial supervision for the implementation of the verdict. All these steps are conducted under the umbrella of legitimacy lest none should be oppressed under the pretext of protecting the rights of society at the expense of individual rights that are guaranteed by divine religions and by the constitutions of different countries. The present paper, therefore, highlights this principle from the legal perspective, and what it insures of criminals guarantees in order to protect their rights from being taken.
Keywords: الفقه الجنائي الإسلامي -- القانون الجنائي -- مبدأ الشرعية الجنائية -- ضمانات المتهم